Progress of cereal transformation technology mediated by Agrobacterium tumefaciens - Hiei, Yukoh; Ishida, Yuji; Komari, Toshihiko (Frontiers in Plant Science, 2014)
Monocotyledonous plants were believed to be not transformable by the soil bacterium Agrobacterium tumefaciens until two decades ago, although convenient protocols for infection of leaf disks and subsequent regeneration of transgenic plants had been well established in a number of dicotyledonous species by then. This belief was reinforced by the fact that monocotyledons are mostly outside the host range of crown gall disease caused by the bacterium and by the failures in trials in monocotyledons to mimic the transformation protocols for dicotyledons. However, a key reason for the failure could have been the lack of active cell divisions at the wound sites, which are the basis of tissue culture and transformation in dicotyledons, in monocotyledons. The complexity and narrow optimal windows of critical factors, such as genotypes of plants, conditions of the plants from which explants are prepared, tissue culture methods and culture media, pre-treatments of explants, strains of A. tumefaciens, inducers of virulence genes, transformation vectors, selection marker genes and selective agents, kept technical hurdles high. Eventually it was determined that rice and maize could be transformed by co-cultivating cells of callus cultures or immature embryos, which are actively dividing or about to divide, with A. tumefaciens. Subsequently, these initial difficulties were resolved one by one by many research groups, and the major cereals are now transformed quite efficiently. As many as 15 independent transgenic events may be regenerated from a single piece of immature embryo of rice. Maize transformation protocols are well established, and almost all transgenic events deregulated for commercialization after 2003 were generated by Agrobacterium-mediated transformation. Wheat, barley and sorghum are also among those plants that can be efficiently transformed by A. tumefaciens.